Human Secretory IgM: An Elusive Player in Mucosal Immunity. Issue 2 (February 2020) - Michaud, Eva; Mastrandrea, Carmelo; Rochereau, Nicolas; Paul, Stéphane
Abstract : Secretory IgMs (SIgMs) were amongst the first identified immunoglobulins. However, their importance was not fully understood and recent advances have shown they play a key role in establishing and promoting commensal gut tolerance in mice and humans. The true interactions between SIgMs and the microbiota remain controversial and we aim to consolidate current knowledge in this review. Through comprehensive examination of SIgMs and their corresponding B cell secretors in several different pathological immunological contexts, we review the presumed role of these molecules in gut tolerance, inflammatory bowel diseases, and lung immunity. As SIgMs harbor a mostly tolerogenic function, we posit that their inclusion in further immunological research is paramount. Highlights: Human secretory immunoglobulin-M (SIgM) is mostly natural IgM and shapes the colonization of mucosal surfaces. SIgMs can selectively bind commensal bacteria at mucosal surfaces and may have overlapping functions with SIgAs in healthy humans and mice. SIgM can regulate B cell development. SIgMs can promote central and mucosal tolerance, which might influence the development and outcomes of autoimmune conditions in mice and humans. The B-1 cell pool produces the bulk of natural IgM and has regulatory functions in the establishment of tolerance in mice. If robustly elicited, SIgM might be potentially beneficial in helping to treat certain pathologies such as infections or autoimmune diseases, although robust testing is still warranted.